Schedules of Fees for Consulting Engineers - Mitchell; Edmund I. (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1921)
VARIOUS suggestions as to proper fees for engineering services have been put forth by individual practitioners and by the American Institute of Consulting Engineers, the Connecticut Society of Civil Engineers, the Iowa Engineering Society and the Mahoning Valley (Ohio) Engineers, for the guidance of both the engineer and his client. The American Institute of Architects also has a schedule of minimum charges (revised 1908). So far as can be determined, however, the four national societies representing civil, mining, mechanical and electrical engineering have never given consideration to this question. An examination of technical periodicals published during the past decade shows that these schedules make provision for three methods of charging; i.e., (A) a percentage of the cost of the completed project; (B) a per diem rate; and (C) a fixed sum. Suggested minimum charges are as follows: